Development of an Intertextual-Based E-Module on Acid–Base Titration Concepts Integrating Science Process Skills - Dea Nabilah Putri; Wiji Wiji; Sri Mulyani; Tuszie Widhiyanti (Universitas Negeri Semarang, 2026)
Students often experience difficulties in understanding chemistry due to their limited ability to connect macroscopic, submicroscopic, and symbolic representations, leading to misconceptions, particularly in acid–base titration. This issue is exacerbated by learning resources that predominantly emphasize symbolic aspects and do not adequately support the integration of multiple representations. To address these challenges, this study developed an intertextual-based e-module that integrates the three levels of chemical representation to support students’ conceptual mastery and Science Process Skills (SPS). This study employed the ADDIE Instructional Model, which consists of five phases: analysis, design, development, implementation, and evaluation. Expert validation involving aspects of chemistry content, pedagogy, language, and media was conducted to assess the feasibility of the e-module. Inter-rater reliability (IRR) percentages were calculated for each aspect, showing high feasibility: content (66.67–100%), pedagogy (100%), language (100%), and media (100%). Feedback from experts was analyzed, and minor revisions were made to improve the quality of the e-module. These results indicate that the intertextual-based e-module is feasible and potentially effective for teaching acid–base titration concepts in high schools. This study contributes to chemistry education by highlighting the integration of intertextual approaches and Science Process Skills within an e-module as a potential way to address students’ difficulties in understanding acid–base titration concepts.